Development amongst the seagrass Cymodocea nodosa influences the morphology of the brown algae Gongolaria barbata in a coastal lagoon of the northern Adriatic Sea - Smith, Shannen M.; Bilajac, Andrea; Gljušćić, Edi; Najdek, Mirjana; Iveša, Ljiljana (Frontiers in Marine Science, 2025)
Marine forests are declining worldwide and understanding the ecology of extant forests is crucial for developing practices that best conserve and restore them for the future. In the Mediterranean region, there has been an increasing effort to restore forest forming fucalean seaweeds and to understand the ecological context that supports their persistence. Here, we describe population metrics for a significant extant fucalean forest located in a coastal lagoon on the southern Istrian peninsula (Croatia). In Šćuza Lagoon, Gongolaria barbata settles within two main substrate types, on small stones and pebbles amongst seagrass Cymodocea nodosa and on rocky substrate provided by larger, more exposed boulders within the meadow but where seagrass does not grow. Amongst seagrass, G. barbata grew to a greater maximum height, observed during both its growth and dormant phases. On boulders, any disadvantage in height appeared to be offset by higher recruitment where the overall density was similar between the two areas. Opportunistic recruitment of G. barbata during the senescent period for C. nodosa appeared to contribute to their coexistence in this unique location and seagrasses appeared to reduce the prevalence of cauloid damage for G. barbata. These findings highlight the importance of understanding fine-scale ecological interactions that support the persistence of isolated patches of vulnerable marine forests.